REVEALING POWER AND SOLIDARITY REFLECTED IN THE USE OF LEXICALIZATION IN HYBRID POLITICAL DISCOURSE: A CASE STUDY IN PRESIDENT OBAMA’S SPEECH AT THE UNIVERSITY OF INDONESIA - Muh. Fajar; Heny Sulistyowati (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
This research was aimed at investigating how President Obama exercised lexicalization as part of their power and solidarity strategy in maintaining in his speech at the University of Indonesia to maintain his good social relations to Indonesian. It employed qualitative reserach by adopting the theory of critical discourse analysis to construct how President Obama constructed his power and solidarity to Indonesian by exercising lexicalization in his speech. The research, furthermore, related the examination of lexicalization and social analysis to get true data analysis of the research. Finally the research described the social relationship between President Obama and the audience. The result of this research showed how President Obama constructed his power  to the audience by choosing positive lexis to his in-group and negative lexis to his out-group. The result showed that their relations are unequal to the opponent. Furthermore, he constructed his solidarity to the audience by exercising his personal experiences and expressing his sad feeling to the audience  of the disaster happened in Indonesia. The result showed that their relations are equal.